2021
DOI: 10.3389/fmicb.2021.636897
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Interaction Between Hepatitis B Virus Infection and Lipid Metabolism in Hepatocytes: A Potential Target of Antiviral Therapy for Chronic Hepatitis B

Abstract: Hepatitis B virus (HBV) is considered a “metabolic virus” and affects many hepatic metabolic pathways. However, how HBV affects lipid metabolism in hepatocytes remains uncertain yet. Accumulating clinical studies suggested that compared to non-HBV-infected controls, chronic HBV infection was associated with lower levels of serum total cholesterol and triglycerides and a lower prevalence of hepatic steatosis. In patients with chronic HBV infection, high ALT level, high body mass index, male gender, or old age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 102 publications
(166 reference statements)
4
35
0
Order By: Relevance
“…In terms of HBV-infected patients, a population prone to liver cancer, this possible lipid-raising effect is of particular interest. HBV infection is associated with lower levels of serum total cholesterol, HDL cholesterol, and TG [ 1 , 2 ]. Furthermore, lower serum cholesterol is associated with more advanced stages of liver disease in this population [ 9 , 59 ], while higher serum cholesterol is associated with better liver cancer survival [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of HBV-infected patients, a population prone to liver cancer, this possible lipid-raising effect is of particular interest. HBV infection is associated with lower levels of serum total cholesterol, HDL cholesterol, and TG [ 1 , 2 ]. Furthermore, lower serum cholesterol is associated with more advanced stages of liver disease in this population [ 9 , 59 ], while higher serum cholesterol is associated with better liver cancer survival [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection affects hosts’ metabolic pathways. It is associated with lower levels of serum total cholesterol, high-density lipoprotein (HDL) cholesterol, and triglycerides (TG) [ 1 , 2 ]. Metabolic syndrome (MetS) is defined as having three or more of the following cardiovascular risk factors: central obesity, elevated TG, reduced HDL-cholesterol, elevated blood pressure, and elevated fasting glucose [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we verified the interaction between MGF360-9L and PSMA3, PSMC1, AMBRA1, and DDX20, a selected cellular protein related to cell metabolism [ 47 , 48 , 49 , 50 ], in vitro by co-immunoprecipitation and IFA. Many viruses, such as Hepatitis B Virus and SARS-CoV-2, hijack the metabolic processes of host cells to escape cellular defense or to acquire substances needed for replication [ 51 , 52 ]. GO, KEGG, and domain analyses of interacting proteins showed that MGF360-9L likely regulates host metabolic response during ASFV infection.…”
Section: Discussionmentioning
confidence: 99%
“…While lipids and their receptors are key players in the early stages of HCV infection, molecules targeting lipids or their receptors could be considered as novel strategies against HCV infection, by preventing or limiting virus-induced damages [ 47 ]. Likewise, HCV, hepatitis B virus (HBV), is considered a metabolic virus, as it affects many hepatic metabolic pathways [ 48 ]. Several studies based on cell lines and mouse models explored the mechanisms by which HBV infection affects lipid metabolism but, to date, results are not conclusive.…”
Section: Changes In Lipid Metabolism During Sars-cov2 Hcv and Hcmv Infectionmentioning
confidence: 99%